Feature Selection for Detecting Fast Attack in Network Intrusion Detection - Abdollah, M. F.; Sahib, S.; Yaacub, A. H.; Othman, M. F. I.; Yusof, R. (Universiti Teknikal Malaysia Melaka, 2008)
Over the last decade, networks have grown in both size and importance especially in exchange data and carry out transactions. They have also become the main mean to attack host. The popularity of intrusion tools and attack scripts are the main contributors of the attacks inside the network.These information gathering techniques can be divided into two categories which are fast attack and slow attack.